Patterning of burnishing head using SU-8 hard mask fabricated by deep X-ray lithography - Maneekat Ch. (2014)
This paper studies on the application of X-ray irradiation from synchrotron light for burnishing head patterning. Feasibility study of SU-8 negative photoresist for AlTiC hard mask in reactive ion etching in CF 4 plasma is investigated and compared with chromium and AZ photoresist. X-ray lithography is used to make SU-8 hard mask on AlTiC substrate, while chromium and AZ hard mask are fabricated by UV lithography. The selectivity ratios between the etching rate of AlTiC and hard mask are investigated to estimate the sufficient mask thickness in the standard AlTiC etch depth of 30 μm. The SU-8 selectivity ratio of 4.46 is enough to create the burnishing head pattern with critical dimension error of 0.86% and the standard deviation of 0.065. Experimental results confirm that SU-8 photoresist is suitable if the process requires another material (non metallic) to decrease manufacturing cost and processing time. © 2012 IEEE.